2022
DOI: 10.3390/pr10050942
|View full text |Cite
|
Sign up to set email alerts
|

Use of Banana Waste as a Source for Bioelectricity Generation

Abstract: The large amounts of organic waste thrown into the garbage without any productivity, and the increase in the demand for electrical energy worldwide, has led to the search for new eco-friendly ways of generating electricity. Because of this, microbial fuel cells have begun to be used as a technology to generate bioelectricity. The main objective of this research was to generate bioelectricity through banana waste using a low-cost laboratory-scale method, achieving the generation of maximum currents and voltages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
2
9
0
2
Order By: Relevance
“…Figure 2c shows the monitored pH values of the microbial fuel cells for thirty days, demonstrating that the values increased from the first day to the last, although these increases were slight in all the MFCs that were kept in the acidic region naturally, without adding chemical compounds. The pH parameter is an important factor in MFCs, mainly for power generation, because the microorganisms that form biofilms on the anodic electrode grow at certain environmental pH values, although this variable varies for each type of cell design and substrate used according to the literature [30,31]; e.g., it has been found that the optimum operating pH for MFCs with banana waste is 4.023 + 0.064, with a peak voltage and current of 1.01 V and 3.71667 [32]. Similarly, Schievano et al (2018) used organic waste, achieving stable pH values of approximately seven at voltage values of 0.08 V on the sixth day of operation [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2c shows the monitored pH values of the microbial fuel cells for thirty days, demonstrating that the values increased from the first day to the last, although these increases were slight in all the MFCs that were kept in the acidic region naturally, without adding chemical compounds. The pH parameter is an important factor in MFCs, mainly for power generation, because the microorganisms that form biofilms on the anodic electrode grow at certain environmental pH values, although this variable varies for each type of cell design and substrate used according to the literature [30,31]; e.g., it has been found that the optimum operating pH for MFCs with banana waste is 4.023 + 0.064, with a peak voltage and current of 1.01 V and 3.71667 [32]. Similarly, Schievano et al (2018) used organic waste, achieving stable pH values of approximately seven at voltage values of 0.08 V on the sixth day of operation [33].…”
Section: Resultsmentioning
confidence: 99%
“…ation, because the microorganisms that form biofilms on the anodic electrode grow at certain environmental pH values, although this variable varies for each type of cell design and substrate used according to the literature [31,32]; e.g., it has been found that the optimum operating pH for MFCs with banana waste is 4.023 + 0.064, with a peak voltage and current of 1.01 V and 3.71667 [33]. Similarly, Schievano et al (2018) used organic waste, achieving stable pH values of approximately seven at voltage values of 0.08 V on the sixth day of operation [34].…”
Section: Resultsmentioning
confidence: 99%
“…Waste fermentation plays an important role in generating the ideal conditions for the acclimatization of electron generating microorganisms, which flow from the anode to the cathode generating electric current. The increase of current values suggests an adhesion of these microorganisms, generating a biofilm to the anode electrode and good reception of the cathode electrode (Rojas-Flores et al, 2022;Saravanan et al, 2021). But substrate degradation in the final stage of monitoring generates an imbalance between oxidation and reduction at the anode and cathode, leading to a decrease in this parameter (Yu et al, 2021).…”
Section: Results and Analysismentioning
confidence: 99%
“…Bin Li [6], realizaron un estudio de caso sobre Vallisneria natans (Lour) Hara"; teniendo como resultados la reducción de arsénico, clorofila y aumento de nivel de dimetilarsinato (DMA), lo que sugería resistencia y detoxificación del As. Igualmente, Fernanda Vidal [9], en su publicación de revista titulada "Fitorremediación de ambientes contaminados con arsénico: Pistia stratiotes L. es una herramienta útil? ", manifiesta que tiene potencial para la fitorremediación de ambientes acuáticos contaminados con concentraciones de Arsénico cercanas a 10 μM.…”
Section: Abstract-the Fishing Port Of Paita Has Been Contaminated By ...unclassified